Echoes of Empire: British Mandate planning in Palestine and its influence in the West Bank today. (2nd January 2017) - Crookston, Martin
ABSTRACT: Almost 70 years after Great Britain gave up its Palestine Mandate, Regional Plans prepared under the Mandate still survive – as live statutory documents that are used to justify planning decisions. Behind them lies a story of how planning is unavoidably tied up with land, with rights, and with power. This article outlines the history of the making of these Plans, explores what the planners of the Mandate epoch thought they were doing, shows how the Plans have been used ever since, and provides an update in the light of a recent UN Habitat Mission to study the planning system under the Israeli occupation. The Plans were the output from the activity of the Mandate government's 'Town Planning Adviser' in the late 1930s and the 1940s – during the period of both the Second World War and the worsening Jewish/Arab violence that led to war in 1947. It was very much a case of the 'export' of town planning from urban and industrial Britain to a society which was primarily rural. The Mandate Plans continue to be used in the formal process by the occupation authorities, but selectively: a selectivity which, unfortunately, the Mandate Plans enable by their flexibility. This bites directly on how Palestinians in the West Bank live – 'the history in the present'.